Transportation, water and environmental geotechnics. Volume 4 proceedings of Indian Geotechnical Conference 2020 - Reddy, C. N. V. Satyanarayana; Saride, Sireesh; Haldar, Sumanta (Singapore Springer, 2021)
This book comprises select proceedings of the Indian Geotechnical Conference 2020 (IGC2020) focusing on emerging opportunities and challenges in the field of transportation geotechnics, scour and erosion, offshore geotechnics, and environmental geotechnology. The contents will be useful to researchers, educators, practitioners and policy makers alike.
Electronic reproduction
Keywords: Geotechnical engineering -- Congresses; Electronic books